KARATERISTIK ORGAN BAGIAN DALAM AYAM BURAS YANG DIBERI PAKAN MINYAK KELAPA (Cocos nucifera) DALAM RANSUM - Leke, Jein Rinny; Sompie, F.N.; Wantasen, E.; Widyastuti, T.; Sondakh, E.H.B. (Universitas Sam Ratulangi, 2019)
INTERNAL ORGANS CHAR ACTERISTICS OF NATIVE CHICKEN FED BY COCONUT OIL (Cocos nucifera) ON DIET. The research was carried to determine the internal organs characteristics of buras chickens fed coconut (Cocos mucifera) oil in diet. A total 100 unsexed buras chickens was used in this experiment. The design used in this study was a completely randomized design (CRD) consisting of 5 treatments and 5 replications (4 hens each). The data were subjected to analysis of variance, when the treatments indicated significant effect it was continued Duncan’s Multiple Range Test. Five dietary treatments containing 0, 0.5%, 1 %, 1,5%, and 2% levels of coconut oil (CO) with five replicates were applied to chickens. Parameters measured were body weight, heart, liver, pancreas and gizzard weight. Result showed that CO in the ration significantly increased the body weight (P<0.01) but did not affect to heart weight, liver weight, pancreas weight and gizzard weight.(P>0.05) It can be concluded that coconut oil in the diet can’t increase the internal organ characteristics. We can gave the 2% CO in the diet for the best results. Key words: Internal Organs, Coconut Oil, Buras Chickens